A Pragmatic Investigation of Khabar Types in al-Sakkākī’s Miftāḥ al-‘Ulūm: Applying Searle’s Speech Act Theory - Athian Sulthon; Dzaki Amrullah; Raswan (Journal of Literature Review, 2025)
Language functions not only as a medium for conveying information but also as a tool for performing actions. The theory of speech acts, introduced by John L. Austin and further developed by John Searle, provides a framework for understanding the pragmatic functions of utterances. In Miftāḥ al-‘Ulūm, al-Sakkākī outlines various types of khabar (declarative statements), each with distinct communicative purposes. This study aims to describe the usage of khabar types in Miftāḥ al-‘Ulūm and to explain their functional correlations based on Searle’s speech act theory. The research adopts a qualitative descriptive method through textual analysis. Primary data were derived from khabar statements in the text, collected through intensive reading, identification, and note-taking, and subsequently classified into Searle’s five categories of speech acts: assertives, directives, commissives, expressives, and declaratives. The findings reveal that the three main types of khabar in Miftāḥ al-‘Ulūm—khabar ibtidā’ī, khabar ṭalabī, and khabar inkārī—predominantly serve assertive, directive, and expressive functions. Khabar ibtidā’ī conveys objective information (assertive); khabar ṭalabī guides the listener from doubt toward acceptance (assertive-directive); while khabar inkārī merges assertive, expressive, and implicit directive functions to affirm truth amid rejection. Commissive and declarative acts are not present, as khabar primarily aims to assert truth rather than induce social status change or future commitments. This study affirms the continuity between classical Arabic rhetoric and the principles of modern pragmatics.